2020
DOI: 10.1093/cdn/nzaa045_086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fresh Mango Fruit Consumption on Glucose, Insulin and Satiety Hormones

Abstract: Objectives A nutrient-dense snack such as fruit may promote greater satiety which may be associated with lower food intake and weight management. Mangos could be a healthful alternative to a less nutritious snack due to its many beneficial dietary compounds. Along with carbohydrates, dietary fiber, and many vitamins and minerals, mangos also have polyphenols and phytochemicals. The purpose of this study was to examine the effect of mangos on postprandial glucose and insulin responses as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In other species, mango ingestion is associated with an increase in adiponectin and cholecystokinin (CCK), which promote satiety for a longer period [ 25 ]. Moreover, bovines that are fed with mangoes showed large increases in ruminal fermentation with impacts on gut health [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other species, mango ingestion is associated with an increase in adiponectin and cholecystokinin (CCK), which promote satiety for a longer period [ 25 ]. Moreover, bovines that are fed with mangoes showed large increases in ruminal fermentation with impacts on gut health [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different experiments have shown that supplementation with concentrates rich in soluble carbohydrates produces ulcers in the squamous region of the stomach [ 1 , 5 , 11 , 21 ] and, in a situation similar to that described in the present work, is correlated with the presence of ulcers. The use of hay alfalfa or continuous forage feeding has been shown to combat stomach acidification by improving chewing and saliva production [ 13 , 14 , 15 , 23 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%